Sustained Usage of Energy Efficient Firewood Cook Stoves and Climate Change Mitigation in Siaya County, Kenya - Omondi , Victor John; Neyole, Edward Masinde; Oteng’, Silvery Buluma (African Journal of Education,Science and Technology (AJEST), 2024)
The importance of using energy efficient firewood cook stoves to reduce fuel consumption and greenhouse gases (GHGs) emissions is widely acknowledged. Consequently, different types of energy efficient firewood stoves have been and continue to be disseminated in many rural households in Kenya. However, the anticipated benefits can be fully actualized only with the sustained longterm usage of these stoves. There has been an existing knowledge gap regarding the link between the sustained utilization of energy-efficient stoves and climate change mitigation in Siaya County, Kenya. This study evaluated the relationship between sustained usage of the energy efficient firewood cook stoves and climate change mitigation. The study employed an experimental design in which 100 households equipped with energy efficient twin brick rocket cook stove were randomly selected. This was followed by a Kitchen Performance Test (KPT), adopting a paired-sample study. Data was analyzed both descriptively and through correlation analysis to test the relationship between the energy efficient stove’s sustained usage and climate change mitigation. The key study finding was that a single twin brick rocket energy efficient cook stove could save approximately 1.1315 tonnes of firewood translating to 1.4099 tonnes of CO2e (41.3%) per year compared to the three stone open fire. The energy efficient stove remarkably reduced firewood consumption and GHGs emissions hence its sustained usage could have tangible impact on climate change mitigation. The study recommends enhanced sensitization on the climate change mitigation benefits of using the energy efficient stoves and scaling up adoption and usage of the energy efficient firewood cook stove through integration of approaches that allow deep understanding of context-specific needs and cooking practices.